Marine Defense Strategy in Securing Indonesian Archipelagic Sea Lanes (ALKI) to Realize Maritime Safety and Maintain Indonesian Sovereignty - Farrolyanto, Rhito (Dinasti Publisher, 2025)
Indonesia is the largest archipelago country in the world consisting of 17,504 islands. Located on the equator and located between the continent of Asia and the continent of Australia, and between the Pacific Ocean and Indian Ocean. Indonesia as an archipelagic country has ratified the United Nation Convention on the Law of the Sea 1982 (UNCLOS 82) and as a consequence Indonesia has established three Indonesian Archipelago Sea Lines (ALKI), namely: ALKI-I, ALKI-II and ALKI-III. The implementation of ALKI rights makes maritime security in Indonesian territory a priority for countries in the world, because disruption of the ALKI route can threaten the world economy and its implementation must be in accordance with UNCLOS provisions. Geographically, Indonesia has a very strategic position in the water sector. Indonesia must be able to control and secure the ALKI route by presenting sea power along the ALKI route in an effort to safeguard the ALKI route, as well as to realize maritime security and defend Indonesia's sovereignty. The purpose of this study is to analyze the marine defense strategy in safeguarding the Indonesian Archipelago Sea Channel (ALKI) to achieve maritime security and defend Indonesia's sovereignty. The data collection method used is the documentation method. The policy of establishing the Indonesian Archipelago Sea Channel (ALKI) has made Indonesia an